Pengaruh Information Sharing terhadap Kinerja Rantai Pasokan Dimoderasi oleh Variabel Distorsi Informasi (Studi pada Pengusaha Bakso Daging Sapi di Kabupaten Lebak, Banten) - Fachrizal, Fikri; Setya, Yanto Azie (Sains: Jurnal Manajemen dan Bisnis, 2017)
Maintain good correlation between the business partners is one of the most important things in build supply chain management. The success of supply chain management cam be seen from how significant the improvement of supply chain performance based on good correlation. This study aims to determine the effect of the correlation between information sharing on supply chain performance that is moderated by variable distortion information. The method that used in this research is quantitative method by descriptive research type. The Respondent in this research are the Entrepreneur of meatball beef by taking 30 samlples that adjusted from each constructed construct. The sample is taking by using porpusive sampling technique. The results of this study indicate that information sharing has a positive and significant impact on supply chain performance, the correlation between information sharing on supply chain performance moderated by information distortion has negative and insignificant effect.